2007
DOI: 10.1097/scs.0b013e3180a03304
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomic Assessment on Perforators of the Lateral Circumflex Femoral Artery for Anterolateral Thigh Flap

Abstract: The anterolateral thigh flap was originally described in 1984 as a septocutaneous flap based on the descending branch of the lateral femoral circumflex artery (LCFA). This flap has many advantages for head and neck reconstruction. However, it is not widely used as a result of the broad range of anatomic variation of the cutaneous perforators and because dissection of these perforators is tedious when they are small. The purposes of this study are to classify the vascular anatomy of the LCFA and to assess the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 20 publications
(14 reference statements)
4
47
0
Order By: Relevance
“…In their case report study, Balachandra et al found the origin of the LCFA to be the deep artery of the thigh and to a lesser degree the femoral artery, which is comparable to previous studies. 28 The study is consistent with the findings made by Dixit et al, Choi et al and Prakash et al 27,29,30 In the findings by Dixit et al, the LCFA was found branching from the deep artery of the thigh in 83.34% in their study cases. Choi et al and Prakash et al found this percentage to be 86.8% and 81.25%, respectively.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In their case report study, Balachandra et al found the origin of the LCFA to be the deep artery of the thigh and to a lesser degree the femoral artery, which is comparable to previous studies. 28 The study is consistent with the findings made by Dixit et al, Choi et al and Prakash et al 27,29,30 In the findings by Dixit et al, the LCFA was found branching from the deep artery of the thigh in 83.34% in their study cases. Choi et al and Prakash et al found this percentage to be 86.8% and 81.25%, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…29 Choi et al found this percentage to be slightly lower, at 13.2% in their study. 30 In the study by Üzel et al this percentage stands at 22.7%. 20 The current study compares closely with the findings by Prakash et al who found this average to be 18.75% in their study sample.…”
Section: Discussionmentioning
confidence: 99%
“…These 2 categorizations of perforators to the ALT flap have traditionally been described. 13,15 However, on imaging analysis, many of the perforator vessels in the present study were observed to traverse both the intermuscular septum along with either the rectus femoris or vastus lateralis muscle. Therefore, a new category of musculoseptocutaneous perforator was created in this study to accurately describe the hybrid vessel path.…”
Section: Imaging Measurementsmentioning
confidence: 60%
“…13,14 Therefore, longitudinal distances are expressed as a percentage of total thigh length from the midpoint (Figure 1). Negative measurements and percentages denote the distance proximal to the mid- point, whereas a positive number denotes a distance distal to the midpoint.…”
Section: Imaging Measurementsmentioning
confidence: 99%
“…Adachi [1] found that LCFA originated from PFA or FA in 78.2% and 13.8% of cases, Siddharth et al [18] in 71% and 16%, Massoud and Fletcher [14] in 81% and 2.8% in their angiographic study, Basar et al [4] in 67.1% and 32.9%, Fukuda et al [9] in 78.2% and 21.4% in their angiographic study, Choi et al [6] in 86.8% and 13.2%, Vasquez et al [25] in 78.8% and 21.2% of cases, Tansatit et al [22] in 56.67% and 43.33% of cases, Uzel et al [24] in 77.3% and 22.7% of cases, Samarawickrama et al [17] in 92.3% from PFA and 8% from common trunk with no from FA, Prakash et al [15] in 81.25% and 18.75% of cases, Dixit et al [8] in 72.8% in right limbs, 77.2% in left limbs and 27.2% in right, 22.8% in left limbs, Anwer et al [2] in 83.33% and 15% of cases, and Sabnis [16] in 80% and 16.6% of cases including the common trunk with PFA. These differences might be in part related to the number of the limbs used in each study or due to an ethnic factor.…”
Section: Discussionmentioning
confidence: 99%